ZNF143 in Chromatin Looping and Gene Regulation - Ye, Bingyu; Yang, Ganggang; Li, Yuanmeng; Zhang, Chunyan; Wang, Qiwen; Yu, Guoying (Frontiers in Genetics, 2020)
ZNF143, a human homolog of the transcriptional activator Staf, is a C2H2-type protein consisting of seven zinc finger domains. As a transcription factor (TF), ZNF143 is sequence specifically binding to chromatin and activates the expression of protein-coding and non-coding genes on a genome scale. Although it is ubiquitous expressed, its expression in cancer cells and tissues is usually higher than that in normal cells and tissues. Therefore, abnormal expression of ZNF143 is related to cancer cell survival, proliferation, differentiation, migration and invasion, suggesting that new small molecules can be designed by targeting ZNF143 as it may be a good potential biomarker and therapeutic target for related cancers. However, the mechanism on how ZNF143 regulates its targeting gene remains unclear. Recently, with the development of chromatin conformation capture (3C) and its derivatives, and high-throughput sequencing technology, new findings have been obtained in the study of ZNF143. Pioneering studies have showed that ZNF143 binds directly to promoters and contributes to chromatin interactions connecting promoters to distal regulatory elements, such as enhancers. Further, it has proved that ZNF143 is involved in CCCTC-binding factor (CTCF) in establishing the conserved chromatin loops by cooperating with cohesin and other partners. These results indicate that ZNF143 is a key loop formation factor. In addition, we report ZNF143 is dynamically bound to chromatin during the cell cycle demonstrated that it is a potential mitotic bookmarking factor. It may be associated with CTCF for mitosis-to-G1 phase transition and chromatin loop re-establishment in early G1 phase. In the future, researchers could further clarify the fine mechanism of ZNF143 in mediating chromatin loops with the help of CUT&RUN (CUT&Tag) and Cut-C technology. Thus, in this review, we summarize the research progress of TF ZNF143 in detail and also predict the potential functions of ZNF143 in cell fate and identity based on our recent discoveries.